Degradasi Total Petroleum Hidrokarbon Oleh Bakteri Petrofilik Dengan Proses Bioremediasi Pada Lahan Pasca Pertambangan Minyak Dan Gas - Rasti, Wilujeng; Syadzadhiya Q. Z Nisa’ (Jurnal Serambi Engineering, 2026)
Soil contamination by petroleum hydrocarbons is a serious environmental problem due to their toxic nature and potential threat to ecosystem health. This study aimed to evaluate the effectiveness of combining biostimulation and bioaugmentation in enhancing the degradation of Total Petroleum Hydrocarbons (TPH) in contaminated soil. The bioremediation experiment was conducted at the laboratory scale using 1000 g of contaminated soil, treated with 20% (w/w) NPK fertilizer and inoculated with Bacillus subtilis and Pseudomonas fluorescens, each at 6% (v/w). The total bacterial population was monitored by determining colony-forming units (CFU/g) following the SNI 2332.3:2015 method, analyzed every 7 days for 35 days. TPH concentration was analyzed using the gravimetric method as regulated in the Decree of the Ministry of Environment No. 128/2003 at the same intervals. The results showed that the bacterial population increased significantly from 9.6 × 10⁸ CFU/g at the beginning of the experiment to 9.30 × 10¹⁵ CFU/g, with the peak growth observed on day 28. TPH concentration decreased consistently throughout the study, indicating that the combination of biostimulation and bioaugmentation was effective in accelerating hydrocarbon degradation.